Alkaline hydrolysis of oil palm empty fruit bunch for enhanced ferulic acid release - Mohd Aanifah, Fairouz Jahaan (2013)
Malaysia is the second largest producer and biggest exporter of palm oil worldwide. Owing to this fact, the biomass produced is in abundance, namely; oil palm empty fruit bunches (OPEFB), mesocarp fibres, palm kernel shells, oil palm fronds and trunks. Among these, OPEFB is the hugely generated lignocellulosic waste. Accordingly, the National Biomass Strategy 2020 was developed to create wealth through biofuels and bio-based chemicals production from excess biomass. Ferulic acid (FA), a hydroxycinnamic acid, exists in various agricultural residues such as maize bran, corn cob, wheat straw and also OPEFB. FA serves as a raw material for production of pharmaceuticals, cosmetics and flavours. It is mainly utilized in flavour synthesis, especially vanilla flavour, due to its property as a precursor for vanillin, the key ingredient of vanilla aroma. FA from nature provides biovanillin through biotechnological route. In order to obtain FA from the OPEFB fibres for biovanillin production, this study was conducted to examine the methods and conditions of FA release from OPEFB fibres through alkaline hydrolysis. The selected treatment strategy (Treatment B1) that involved autoclaving OPEFB fibres (120°C, 3 hours) followed by alkaline hydrolysis (90°C, 3 hours, agitated at 120 rpm in water bath shaker), showed significant yield of FA release from OPEFB fibres. Alkaline hydrolysis using 0.5 to 5.0% (w/v) of NaOH, KOH and K2CO3 gave both 2.0% (w/v) KOH and NaOH as the best alkalis concentration for better FA release from OPEFB fibres compared to other alkali concentrations. The addition of 98 μL sodium bisulfite (NaHSO3) to KOH treatment yielded 4.23 mg/L higher FA compared to the hydrolysis without NaHSO3 as it reduced repolymerization and oxidation of FA. It was also observed that the FA release was affected by the different reaction times at high and ambient temperature during alkaline hydrolysis. FA was observed to decrease due to longer hydrolysis time at high temperature and treatment at 37°C for 16 hours yielded only an average of 24 to 42 mg/L FA only. About 66.18 ± 3.24 mg/L and 56.94 ± 3.52 mg/L FA was released using 2.0% (w/v) NaOH and KOH, respectively through Treatment B1 (with the addition of NaHSO3) from the esterified FA in the OPEFB fibres. Fourier transform infrared (FTIR) analysis showed evidence of decrease in aromatic groups, lignin and ester linkages stretching thus showed that FA, the lignin monomer has been released from OPEFB fibres. It was suggested that mild alkaline hydrolysis was sufficient in solubilising FA that is esterified in the OPEFB lignin and hemicellulose.